Isolasi dan Purifikasi Inhibitor α-amilase dari Biji Kacang Phaseolus vulgaris - Husin, Bahagiawati A. (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2005)
Plant genetic engineering technologies enable of introducing insect resistance genes into crop plants. The cry genes, genes encoding for inhibitor of digestive enzymes of a target insect that were isolated from Bacillus thuringiensis can be used for this purpose. Seeds of common bean (Phaseolus vulgaris) contain a glycoprotein that inhibits activity of α-amylase of insects. A α-amylase inhibitor was purified from the common bean seeds. The purified α-amylase inhibitor was then fed to cowpea storage weevil, Callosobruchus maculatus. The results showed a lengthened larval development time inside the seed and caused mortality to the insect larvae. This experiment suggests that the α-amylase inhibitor gene from the common bean seed could be used as a candidate gene for genetic engineering of plant resistance to bruchid insects.